Geographical indications for agricultural and handicraft goods. The strength of the link to the origin as a criterion - Marie-Vivien, Delphine; Biénabe, Estelle (Perspective, 2012)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The recognition of geographical indications (GIs) by the World Trade Organization (WTO) has led many countries to establish a specific legal framework to protect their traditional local products, whether agricultural, foodstuff or handicraft. These changes are taking place within a heterogeneous international legal context. The European Union, for example, only protects GIs for agricultural products and foodstuffs. This regulation deprives designations of traditional handicraft goods, which are numerous in the countries of the South, of protection on the European market, and fosters risks of misuse. Historical analysis of the protection of GIs and practices in Europe and India nevertheless show that there is no justification for treating products differently according to their nature. Hence the proposal to create a new international and European legal framework based on the strength of the link between the product and its geographical origin. The strength of this link would be assessed using criteria pertaining to natural and human factors, whether individually or combined, which are relevant whatever the product is."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The recognition of geographical indications (GIs) by the World Trade Organization (WTO) has led many countries to establish a specific legal framework to protect their traditional local products, whether agricultural, foodstuff or handicraft. These changes are taking place within a heterogeneous international legal context. The European Union, for example, only protects GIs for agricultural products and foodstuffs. This regulation deprives designations of traditional handicraft goods, which are numerous in the countries of the South, of protection on the European market, and fosters risks of misuse. Historical analysis of the protection of GIs and practices in Europe and India nevertheless show that there is no justification for treating products differently according to their nature. Hence the proposal to create a new international and European legal framework based on the strength of the link between the product and its geographical origin. The strength of this link would be assessed using criteria pertaining to natural and human factors, whether individually or combined, which are relevant whatever the product is."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">The recognition of geographical indications (GIs) by the World Trade Organization (WTO) has led many countries to establish a specific legal framework to protect their traditional local products, whether agricultural, foodstuff or handicraft. These changes are taking place within a heterogeneous international legal context. The European Union, for example, only protects GIs for agricultural products and foodstuffs. This regulation deprives designations of traditional handicraft goods, which are numerous in the countries of the South, of protection on the European market, and fosters risks of misuse. Historical analysis of the protection of GIs and practices in Europe and India nevertheless show that there is no justification for treating products differently according to their nature. Hence the proposal to create a new international and European legal framework based on the strength of the link between the product and its geographical origin. The strength of this link would be assessed using criteria pertaining to natural and human factors, whether individually or combined, which are relevant whatever the product is.